MOTIVATING FACTORS OF FARMERS TO ENGAGE VEGETABLE-BASED AGRIBUSINESS IN EAST JAVA AND BALI, INDONESIA - Mariyono, Joko (Muhammadiyah University Press, 2019)
Vegetable crops play an important role in the Indonesian economy through their multiplier effect in farm household livelihoods. This paper analyses factors that determine farmers to commercialize vegetable-based agribusiness ventures. Intensive vegetable farming, as a part of agricultural commercialization, is considered a technological package that is more profitable, and high input and labor intensive compared to rice and other cereal crops. The study employed a qualitative approach to describe the farmers? motivation. Data for this study were compiled from surveys conducted in 2014 by interviewing 357 farm households, which were located in four major vegetable producing regions of East Java and Bali, Indonesia. Qualitative surveys and descriptive statistics approaches were used to support the quantitative regression models. Results show that farmers were more motivated to commercialize because of economic and agro-ecological reasons. An enabling agribusiness environment such as access to good produce markets, credit, as well as market information and support systems access are expected to be other driving factors boosting commercial vegetable farming and associated steady growth of vegetable production in Indonesia. Vegetable markets should be emphasized in the potential vegetable producing regions of Indonesia.